Material specific information from objects in absconditus for warhead dismantlement verification - Smith, Kerrie L. (Cranfield University, 2019)
Material specific information from objects in absconditus for warhead dismantlement verification A long-standing problem within nuclear disarmament is that there are no established methods to verify that a nuclear weapon (NW) has been dismantled according to the treaties in place. The Nuclear Non-proliferation Treaty(NPT), the treaty that aims to reduce the stockpiles of nuclear weapons, also encourages research into technologies to verify the disarmament without compromising sensitive information. During the dismantlement process, inspectors have limited access to the nuclear weapons under dismantlement and similarly there are also restrictions on the containers the weapon components are stored in once separated. This project examines the development of a verification method to attest the presence, or indeed absence, of the high explosive component of a nuclear weapon. Various bulk detection methods have been reviewed and X-ray diffraction (XRD) was found to be a promising method that would, at high energy, permit the penetration of metal containers and have the sensitivity needed to identify the explosive. Conventional pencil beam geometry of XRD was used to demonstrate the feasibility of the technique. One of the fundamental requirements to identify a material viaXRD is to have knowledge of the location of the scattering source. Several novel techniques were established and considered to enable depth perception with angular dispersive XRD (ADXRD) along the primary axis including an analytical method, novel post-sample encoders (linear wire and Archimedean spiral) and the successful development and introduction of an algorithm by which the diffraction data is compared to a set database of materials to produce a likelihood of materials at specific locations. Focal construct geometry (FCG)-which uses a hollow conical incident beam – was introduced as a method to increase the number of photons available and hence offer enhanced diffraction data with improved intensity. Although useful in situations where the high penetration is not required, ADXRD is limited by the characteristic peak, meaning it cannot penetrate through highly absorbing materials such as metals. Higher energy photons can be utilised if energy dispersive XRD (EDXRD) is considered. The use of high energy sources was evaluated in terms of their efficiency at generating photons contributing to EDXRD than of the characteristic peaks, ADXRD. It was found that, the higher the voltage of source, the higher the proportion of photons to EDXRD than that of the characteristic peaks. As with the conventional pencil beam geometry, post-sample encoders were introduced to enable depth perception along the primary axis. The post=sample pin hole encoder allowed for the first time the explosive diffraction signature to be separated from the concealments’ diffraction, a limitation of the pencil beam techniques introduced here. The depth resolution of the technique was evaluated analytically to indicate possible improvements to increase detectability of concealed objects. Simulations were conducted enabling a comparison with experimental data and then extended to higher energy via simulation, to provide an indication of the potential sue and any limitations that may arise. Overall this project is the first to demonstrate that XRD is a potentially viable technique for material phase identification behind highly absorbing metal barriers and has introduced several novel techniques for depth perception including post=sample encoders and a new algorithm for ADXRD diffraction profiles. Furthermore, this thesis is the first instance of FCG XRD being identified and applied to the problem of nuclear weapon dismantlement verification with the capability to identify and locate concealed explosives inside highly absorbing containers, advancing the possibility to aid the verification of nuclear warhead dismantlement.